Effectiveness of molnupiravir for treating COVID-19 in patients with psychiatric disorders - Liu, Ting-Hui; Liao, Hsuan-Yi; Chang, Chih-Cheng; Lai, Chih-Cheng (Frontiers in Pharmacology, 2024)
Objectives: This study investigated the clinical effectiveness of molnupiravir for treating non-hospitalized COVID-19 patients with pre-existing psychiatric disorder.This retrospective cohort study used the TriNetX research network to identify patients with psychiatric disorder who experienced non-hospitalized COVID-19 between January 1, 2022, and May 1, 2023. The propensity score matching (PSM) method was used to match patients receiving molnupiravir (treated group) with those who did not (untreated group). The outcome included short-term outcomes -the composite of all-cause hospitalization or death within 30 days and the risk of post-COVID-19 conditions up to a year after COVID-19 diagnosis.Results: Two groups of 9,421 patients, each with balanced baseline characteristics, were identified using the PSM method. During the 30-day follow-up, treated group was associated with a reduced risk of hospitalization or mortality compared to untreated group (HR, 0.760; 95% CI, 0.665-0.869). Compared to untreated group, treated group also exhibited a decreased risk of experiencing post-COVID-19 conditions, including chest/throat pain (HR, 0.615; 95% CI, 0.543-0.696), abnormal breathing (HR, 0.761; 95% CI, 0.687-0.884), abdominal symptoms (HR, 0.748; 95% CI, 0.674-0.831), fatigue (HR, 0.718; 95% CI, 0.638-0.808), headache (HR, 0.753; 95% CI, 0.665-0.852), cognitive symptoms (HR, 0.769; 95% CI, 0.630-0.940), myalgia (HR, 0.647; 95% CI, 0.530-0.789), cough (HR, 0.867; 95% CI, 0.770-0.978), and palpitation (HR, 0.641; 95% CI, 0.534-0.770) during the one-year follow-up.Molnupiravir could be associated with lower rates of all-cause hospitalization or death and also lower risk of post-COVID-19 condition among nonhospitalized COVID-19 patients with pre-existing psychiatric disorder.